Durability of cement-stabilised rammed earth: a case study in Western Australia. Issue 1 (1st January 2016) - Beckett, C.T.S.; Ciancio, D.
Abstract : Cement-stabilised rammed earth (CSRE) is a popular building material in Australia due to its natural aesthetic, good thermal properties and environmental appeal. However, little work has been done investigating the effect of long-term exposure to environmental conditions on its durability. This paper presents a case study investigating the aged properties of material obtained from a 32-year-old CSRE wall in Perth, WA. Core samples were obtained for unconfined compressive strength testing and compared to results found for 28-day-old specimens, manufactured using the same material and nominal compaction regime, to investigate changes in material strength over time. Sample wall sections were also obtained to determine material volume losses due to erosion. Results found for 32-year- and 28-day-old material are compared taking into account local climate conditions to comment on the suitability of current laboratory methods for predicting degradation of CSRE materials. Loss of strength due to exposure is found to be significant in this study. This result suggests that, when designing for the longevity of exposed CSRE materials, ageing strength is an important factor that should not be neglected.